Socialization about Anemia and First Aid for Fainting Teenagers in Gunung Pancar Village, Bogor - Reviani, Nia; Natasha, Margaretha Maria Odilia; Marisa, Nadiya; Kristanti, Agata; Suryanegara, Wiradi (International Journal of Community Service (IJCS), 2025)
Anemia is a common health problem in the community, especially among adolescents and women of childbearing age. One clinical manifestation of anemia or other conditions frequently found in schools and the community is fainting. Lack of knowledge about anemia and the public's lack of knowledge regarding first aid for fainting can result in delayed treatment and an increased risk of complications. This community service activity aims to increase participants' knowledge about anemia prevention and basic skills in providing first aid to fainting patients. The method used was interactive counseling supplemented by demonstrations and simulations, as well as evaluation through pre- and post-tests. The activity was held at Pancar Bakti Junior and Senior High Schools, Gunung Pancar, Bogor, and was attended by 100 participants. The results showed an increase in the average understanding score of participants from 58 (pre-test) to 85 (post-test), with active participation in the discussion and simulation sessions. In conclusion, this outreach activity was effective in increasing participants' basic knowledge and skills regarding anemia and first aid for fainting, and can be used as a promotional and preventive effort in the community.